2021
DOI: 10.1007/978-3-030-64308-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Mud Volcanoes

Abstract: The eruption of mud and magma can be influenced by earthquakes and reports date back more than 2000 years. Dozens of examples of eruptions have now been documented in response to both static and dynamic stresses from earthquakes. Already erupting systems are most sensitive to earthquakes compared to initiating new eruptions. Multiple plausible mechanisms have been proposed for triggering eruptions including disrupting particle-rich materials, mobilizing bubbles, or changing permeability—changes may occur both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…They are hazardous phenomena, because as of today, it is impossible to define the parameters for modelling the recurrence intervals of the extreme events (Gattuso et al, 2021). Azerbaijan hosts some mud volcanoes where the most violent eruptions worldwide are recorded; the Lökbatan mud volcano, for example, ex-plodes every 3-5 years in spectacular eruptions, which send detritus and breccia rafts into the Caspian Sea (Mazzini et al, 2021;Wang and Manga, 2021). In recent times (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016), the massive eruption of the Indonesian Lusi mud volcano, triggered by the drilling of a borehole, continued for years with peak mudflows of 180 000 m 3 d −1 that caused the burial of nearby villages and the displacement of 60 000 people (Mazzini et al, 2007;Tingay, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They are hazardous phenomena, because as of today, it is impossible to define the parameters for modelling the recurrence intervals of the extreme events (Gattuso et al, 2021). Azerbaijan hosts some mud volcanoes where the most violent eruptions worldwide are recorded; the Lökbatan mud volcano, for example, ex-plodes every 3-5 years in spectacular eruptions, which send detritus and breccia rafts into the Caspian Sea (Mazzini et al, 2021;Wang and Manga, 2021). In recent times (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016), the massive eruption of the Indonesian Lusi mud volcano, triggered by the drilling of a borehole, continued for years with peak mudflows of 180 000 m 3 d −1 that caused the burial of nearby villages and the displacement of 60 000 people (Mazzini et al, 2007;Tingay, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Deformation and decreasing strength of rocks under the compressional stress field can be a driving or triggering force for mud volcanism (Soto et al, 2021a;. Seismic activities that occur nearby can also trigger mud volcanisms (Manga et al, 2009;Wang and Manga, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The ejected materials comprise gas, mainly CH 4 and CO 2 , mud, rock fragments, and water (Kopf, 2002), which are thought to be related to natural gases, petroleum, and/or gas hydrates (Etiope et al, 2009;Tinivella and Giustiniani, 2012). Some studies have indicated that earthquakes trigger MV activities (e.g., Tsunogai et al, 2012), but not all earthquakes are associated with MVs (Manga et al, 2009;Tingay et al, 2018;Wang and Manga, 2021). To investigate causal relationships, it is essential to monitor MV activity.…”
Section: Introductionmentioning
confidence: 99%